2018
DOI: 10.1021/acsami.8b16505
|View full text |Cite
|
Sign up to set email alerts
|

KAgSe: A New Two-Dimensional Efficient Photovoltaic Material with Layer-Independent Behaviors

Abstract: Recent advances in the development of two-dimensional (2D) materials have stimulated people’s interest and enthusiasm to discover new kinds of 2D functional materials. In this paper, we propose a novel 2D layered semiconductor KAgSe using the first-principles calculation method, which displays excellent photovoltaic properties with proper direct band gap and significant carrier mobility. By evaluating the cohesive energy, vibrational phonon spectrum, and temporal evolution of the total energy at a high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 68 publications
6
37
0
Order By: Relevance
“…For both MoSi 2 P 4 and MoSi 2 As 4 , the photocurrent is roughly symmetrical with respect to θ = 90 • , and reaches maximums at θ = 0 • and θ = 180 • . Similar symmetrical distribution of photocurrent with polarization angle was also reported for monolayer KAgSe-based 2D optoelectronic device [40].…”
Section: Photocurrent In Monolayer Mosi 2 Z 4 Nanodevicesupporting
confidence: 84%
See 2 more Smart Citations
“…For both MoSi 2 P 4 and MoSi 2 As 4 , the photocurrent is roughly symmetrical with respect to θ = 90 • , and reaches maximums at θ = 0 • and θ = 180 • . Similar symmetrical distribution of photocurrent with polarization angle was also reported for monolayer KAgSe-based 2D optoelectronic device [40].…”
Section: Photocurrent In Monolayer Mosi 2 Z 4 Nanodevicesupporting
confidence: 84%
“…For bilayer MoSi 2 Z 4 , the rather weak interlayer vdW interaction makes the Mo atoms at the up layer and those at the down layer have nothing to do with each other, and thus the band gap is very close to that of the monolayer. Similar layer number independent bandgap behavior has also been found in layered 2D KAgSe [40]. The layer number independent electronic properties provide enormous convenience and less difficulty in experimental fabrication of finite layer MoSi 2 Z 4 -based electronic devices.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Recently (2018), Wang et al [13] explored KAgSe and reported it to be an efficient photovoltaic material in 2D, possessing layer-independent behaviours. According to these authors, KAgSe is a stratified material having alternating layers of K-Se-Ag-Se-K along the (001) direction.…”
Section: Introductionmentioning
confidence: 99%
“…Together with these impressive developments in materials predictions, recent progresses in the data-driven sciences such as text-mining and natural language processing for synthesis of inorganic materials [16] may further accelerate the computer-aided materials discovery. For 2D materials, high-throughput materials search algorithms [8,9,17,18] have been used for screening the optimal material candidates for solar cell applications [17][18][19][20][21]. Considering current domination of silicon solar cells, however, a suitable 2D silicon material that is readily applicable for harvesting solar light is still lacking.…”
mentioning
confidence: 99%